2023
DOI: 10.1021/jacs.2c12986
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Separable Nanovaccines with Stealthy Bioadhesive Capability for Durable Cancer Immunotherapy

Abstract: Because of tumor heterogeneity and the immunosuppressive tumor microenvironment, most cancer vaccines typically do not elicit robust antitumor immunological responses in clinical trials. In this paper, we report findings about a bioadhesive nanoparticle (BNP)-based separable cancer vaccine, FeSHK@B-ovalbumin (OVA), to target multi-epitope antigens and exert effective cancer immunotherapy. After the FeSHK@B-OVA "nanorocket" initiates the "satellite-rocket separation" procedure in the acidic tumor microenvironme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…It had also been reported that activation of T cell-related immunity by nanomedicine could trigger a strong immune response and robust immune memory effects, which could effectively inhibit tumor growth for a prolonged period. 55,56 The macrophage results were in accordance with the immunofluorescence results. Compared with the PBS group, NPs loaded with motolimod significantly increased the expression of TNF-α and decreased the expression of CD206 on F4/80 + macrophages, while TNF-α and CD206 in the other groups showed no changes.…”
Section: Effects Of Ros Produced By Repolarized Tams On the Function ...supporting
confidence: 83%
“…It had also been reported that activation of T cell-related immunity by nanomedicine could trigger a strong immune response and robust immune memory effects, which could effectively inhibit tumor growth for a prolonged period. 55,56 The macrophage results were in accordance with the immunofluorescence results. Compared with the PBS group, NPs loaded with motolimod significantly increased the expression of TNF-α and decreased the expression of CD206 on F4/80 + macrophages, while TNF-α and CD206 in the other groups showed no changes.…”
Section: Effects Of Ros Produced By Repolarized Tams On the Function ...supporting
confidence: 83%
“…Studies indicated that immune cell infiltration in the tumor microenvironment is closely related to tumor progression. , To investigate changes in the immune tumor microenvironment after the treatment, the mice were sacrificed on day 14, and the tumor-infiltrating immune cells were analyzed by flow cytometry (Figure S9b). The results showed that the number of APCs (Figure g,h) in the tumors after G5 treatment was significantly higher than that of other treatments, indicating the induction of an immunostimulatory tumor microenvironment after ISAMn-MOF treatment without causing body weight loss in the mice (Figure S9c).…”
Section: Resultsmentioning
confidence: 99%
“…[4,21,35] Therefore, we used a 2,7-dichlorofluorescein diacetate (H 2 DCF-DA) staining assay to monitor the intracellular ROS expression of the treated macrophages. [23,[36][37][38] Fluorescence microscope images showed that M2-like macrophages treated with STNSP or β-Elemene induced the generation of intracellular ROS in a dose-dependent manner (Figure 2a, 2b and S6). Moreover, STNSP@ELE-treated macrophages displayed the highest intracellular ROS level (Figure 2a and 2b).…”
Section: Mechanism Of M1-like Macrophage Polarization and Therapeutic...mentioning
confidence: 99%